Faktor-Faktor yang Berhubungan dengan Kelelahan Mata pada Penjahit di Kecamatan Lubuk Alung Kabupaten Padang Pariaman Tahun 2021 - Sri Mindayani; Novia Zulfa Hanum; Nurhayati Biabdihil Hamidah (Ilmu Bersama Center, 2022)
Eye fatigue is caused by continuous use of the eyes. The incidence of asthenopia in the world is an average of 75% per year, another study found that the prevalence of asthenopia is 49.4%. The purpose of this study was to determine the factors associated with eye fatigue in tailors in Lubuk Alung District, Padang Pariaman Regency in 2021. This type of research is an analytical survey research method with a cross sectional approach. The population is 41 using a sampling technique, namely Total Sampling, which is 41 tailors. The research was carried out from January to September 2021 using survey and interview techniques and taking measurements with the Luxmeter tool. Data were analyzed univariately using frequency distribution and bivariate analysis using Chi-Square test with 95% confidence level <0.05.The results showed that there were 23 (56.1%) tailors experienced severe eye fatigue, 20 (48.8%) tailors had a risky work attitude, 28 (68.3%) tailors worked with lighting that did not match the NAV (<500 Lux and >1000 lux, and 38 (92.7%) tailors with a working period at risk.There is a relationship between work attitude and eye fatigue (P = 0.007), there is no relationship between lighting intensity and eye fatigue (P = 0.059), there is no relationship working period with eye fatigue (P=0.077). It is expected that tailors work with an ergonomic work attitude, not too close to the object being worked on and do stretching and eye exercises after doing work so as not to experience eye fatigue and adjust lighting in accordance with NAV in the workplace.